Mapping of Groundwater Flow Pattern and its Quality Index based on Microbiological Parameters in Klojen District, Malang City, East Java, Indonesia - Permata, Veronika Yulia; Siswoyo, Hari; Haribowo, Riyanto (Civil and Environmental Science Journal (CIVENSE), 2021)
Groundwater is one source of fulfilling water needs for the Klojen district, the most populous district in Malang City. Population density affects the condition of groundwater quality because it causes pollution. The possibility of groundwater quality contamination can be identified by mapping the flow pattern and determining the quality level according to its use as drinking water. The purpose of this study is to map the groundwater quality index according to its flow pattern. Flow patterns based on groundwater-surface contours can indicate the direction of flow and the direction of pollution. The quality of groundwater according to its use as drinking water was identified using the Weighted Arithmetic Water Quality Index (WAWQI) method. Based on the research results, the research location's flow pattern generally flows from North to South. According to the flow pattern, groundwater quality is getting worse, as indicated by an increase in the index value.